Association of mortality with fludrocortisone addition to hydrocortisone treatment among septic shock patients: a propensity score matching analysis - Cheng, Xiaoxiao; Fu, Zhiqin; Liu, Yiting; Zheng, Xiaoyu; Hu, Tianyang (Frontiers in Medicine, 2023)
Background: Several clinical trials of corticosteroids have been carried out in the treatment of septic shock, however, the therapeutic effect of the most widely used hydrocortisone is still controversial, and no studies have directly compared hydrocortisone versus hydrocortisone plus fludrocortisone for patients with septic shock. Methods: Baseline characteristics and treatment regimens of patients with septic shock treated with hydrocortisone from the Medical Information Mart for Intensive Care-IV database were collected. Patients were divided into hydrocortisone treatment groups and hydrocortisone plus fludrocortisone treatment groups. The primary outcome was 90-day mortality, and secondary outcomes included 28-day mortality, in-hospital mortality, length of hospital stay, and length of intensive care unit (ICU) stay. Binomial Logistic regression analysis was performed to identify independent risk factors for mortality. Survival analysis was performed and Kaplan-Meier curves were drawn for patients in different treatment groups. Propensity score matching (PSM) analysis was performed to reduce bias. Results: Hydrocortisone plus fludrocortisone did not reduce the 90-day mortality, 28-day mortality and in-hospital mortality of the enrolled patients, nor did it affect the length of hospital stay and ICU stay, and there was no statistically significant difference in the corresponding survival time. The Simplified Acute Physiology Score II (SAPS II) score was an independent risk factor for 28-day mortality and in-hospital mortality. Conclusions: In the treatment of patients with septic shock, hydrocortisone plus fludrocortisone did not reduce 90-day mortality, 28-day mortality, and in-hospital mortality compared with hydrocortisone alone, and had no effect on the length of hospital stay and ICU stay.